PENINGKATAN KETERAMPILAN MEMBACA AKSARA JAWA MELALUI MEDIA AUDIOVISUAL PADA SISWA KELAS V SD NEGERI 2 PADOKAN BANTUL - Khusna Arimas; Siti Anafiah (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aims to describe the improvement of Javanese literacy skills through audiovisual media in 2 Padokan Bantul State Elementary School. The application of audiovisual media can improve the reading skills of Javanese script in the fifth-grade students of 2 Padokan Bantul State Elementary School. This research is a Classroom Action Research (CAR). The subject of this research was all the fifth-grade students of 2 Padokan Bantul State Elementary School Academic Year 2018/2019 which amounted to 31 students. Data collection techniques used observation, testing, and documentation techniques. The results of this research indicate that after using audiovisual media, students' reading literacy skills can increase. The increase can be seen from the percentage of the students whose grades reached KKM (75). Before the action was taken, the percentage of the students who reached KKM was still lacking, 32.26%. After the first cycle of action, the percentage of the students who reached KKM increased to 50.84%. At the end of the second cycle, the percentage of the students who reached KKM increased to 80.64%. These results are following the criteria for the success of the prescribed actions, namely â‰¥75% of the students get scores above the KKM (75).